Department of applied linguistics: heritage and modernity - Darahakupets-Navitskaya, Aksana M. (Journal of the Belarusian State University. Philology, 2024)
The issue of the formation and development of applied linguistics at the faculty of philology of the Belarusian State University is covered. The activities of the department of applied linguistics at the present stage are characterised. The directions of educational, methodological, scientific, cultural and educational activities of the department’s staff are identified. The importance of developing theoretical foundations and practical application of innovative methods of teaching Russian as a foreign language is shown, taking into account the goals and objectives of intercultural communication. The main achievements of the department over the recent period are mentioned. The importance of international cooperation in the field of science and education which is given special attention at the department is noted.